Zika virus public health crisis and the perpetuation of gender inequality in Brazil - Raquel Zanatta Coutinho; Aida Villanueva; Abigail Weitzman; Letícia Junqueira Marteleto (BMC, 2021)
Abstract Background In 2015-2017, the Americas experienced a highly consequential epidemics for pregnancy and childbearing. Mainly transmitted by the mosquito Aedes aegypti, but also through sexual intercourse, the Zika virus poses the risk of congenital Zika syndrome to fetus, which includes microcephaly and other child development complications. When a public health crisis taps directly into reproductive health, typically a feminine realm, responses to the emergency may exacerbate deeply-rooted gender norms. This paper investigates the role of gender in two relational contexts: (a) the government-led response to the pandemic in terms of communication campaigns aimed at preventing Zika infections; and (b) an individual level of response to the emergency, concerning women's negotiation with their sexual partners with regard to the prevention of Zika as well as pregnancies. Methods We conducted content analysis of 94 unique pieces from public health communication campaigns produced by governmental agencies with the goal of promoting Zika awareness. Print and online materials were collected from May 2016 to August 2017, and included TV ads, Internet Pop-ups, and pamphlets. We also analyzed transcripts from 16 focus groups conducted with reproductive-aged women (18-40) in Belo Horizonte and Recife, two large cities differently affected by the Zika outbreak. Women answered open-ended questions connected to the epidemic, in areas such as personal knowledge and experiences with the Zika virus, experiences of their friends and acquaintances, their primary information sources, their perceptions of public health efforts toward containing the outbreak, as well as women's contraceptive use. Results Campaign pieces handling pregnancy and microcephaly were largely gendered. Pieces targeted women, placing on their shoulders the responsibility for protecting a potential fetus from the disease. Importantly, campaigns neglected addressing male's participation on Zika prevention and contraceptive management, while failing to take into account Brazil's large proportion of unplanned pregnancies. Women were placed in a double bind by being expected to prevent both pregnancy and Zika, in a context where gendered power imbalances often translate in women having little power/means for condom negotiation/avoiding unprotected sexual intercourse. Conclusion Government and individual responses to the epidemics reinforced gender roles, situating pregnant women as responsible for averting mosquito bites and microcephaly. Further, prevention campaigns largely excluded men. Since low-socioeconomic status women possessed fewer resources to preclude infection, we also found that beyond the gender divide, this subgroup faced more pronounced Zika prevention challenges as they found it harder to negotiate condom use with their sexual partners and often could not access other types of contraceptives resulting in unplanned pregnancies.